Recursos educativos audiovisuales en el desarrollo de las competencias comunicacionales en el cuarto grado de la Unidad Educativa José Ingenieros, Loja 2023-2024 - Caraguay Gallegos, María del Carmen (2024)
The present research called Audiovisual Educationa8l Resources in the development of communicational competencies in the fourth grade of the José Ingenieros Educational Unit, Loja 2023-2024, had the following general objective: To analyze the incidence of audiovisual educational resources in the development of communicational competencies in the fourth grade of the José Ingenieros Educational Unit, Loja 2023-2024. The specific objectives were: To diagnose the communicational competencies that students have developed during their learning process; To design an improvement proposal based on audiovisual educational resources for the development of communicational competencies in students; To evaluate the improvement proposal based on audiovisual educational resources for the development of communicational competencies in students. The present research was of an exploratory- descriptive type with a mixed approach of quasi-experimental design, likewise, methods such as the scientific, synthetic, inductive, analytical, deductive and statistical method were used; the techniques used were the interview, pre- and post-evaluation; The instruments used were the structured questionnaire and the pre- and post-evaluation questionnaire; the population consisted of teachers and students of the elementary sub-level of the José Ingenieros School of Basic Education, whose sample consisted of one teacher and 32 students of fourth grade "A", for which a non-probabilistic sampling was used. Likewise, it is important to mention that the use of audiovisual educational resources is beneficial because it facilitates the understanding and development of communication skills in students, since their learning takes place through different audiovisual resources such as images, videos, podcasts and audiobooks. Undoubtedly, this is productive since the student learns in an active, dynamic and participative way.